Relevance Net Income, Equity, Operating Cash Flow of Stock Prices Moderated Firm Size - Diah Maya; Putri Awalina; Miladiah Kusumaningarti (LP2M IAIN Palopo, 2026)
This study aims to examine the value relevance of net income, book value of equity, and operating cash flow on stock prices of property sector companies listed on the Indonesia Stock Exchange, with firm size as a moderating variable. A quantitative method was used involving multiple linear regression and Moderated Regression Analysis (MRA). The study used secondary data derived from financial statements and stock price data of property sub-sector companies during the 2021–2024 period. Statistical analysis was conducted using SPSS software. The findings indicate that while net income and book value of equity lack significant impact, operating cash flow does positively and significantly impact stock price. Firm size moderates the relationship between book value of equity and stock prices by weakening this relationship. Operating cash flow has a positive and significant effect on stock prices of property sector companies listed on the Indonesia Stock Exchange during 2021–2024, while net income and book value of equity show no significant direct effect. Firm size weakens the relationship between book value of equity and stock prices, indicating that investors emphasize cash-based information in firm valuation. This study is limited to property sector companies and a specific post-pandemic period. This study contributes to value relevance literature by emphasizing the importance of operating cash flow information for investors in valuing property sector companies.